Metaphysical Analysis and Mystical Knowledge in Guidance and Counseling - Ice Desvikayati; Yeni Karneli; Sufyarma Mursidi; Ramadani (Quality : Journal Of Education, Arabic And Islamic Studies, 2025)
Guidance and counseling continues to develop and must be able to adapt to current developments. This research examines the integration of metaphysics and mystical knowledge in the context of guidance and counseling. This approach aims to explore the potential benefits, challenges, and practical implications of adopting metaphysical and mystical elements in counseling practice. The research method used is analysis of documents and related articles, with a focus on theories that support the use of metaphysics and mysticism in supporting personal growth and client psychological well-being. The results of the analysis show that this integration can increase self-understanding, provide transformative experiences, and improve overall well-being. However, challenges such as conformity with clients' values and the need for adequate counselor training were also identified. The study concludes by suggesting the need for a holistic and culturally sensitive approach in implementing these techniques, as well as a call for further research in measuring the effectiveness and adaptability of these approaches for various client populations.